PERAN EMOSI POSITIF MEMEDIASI PENGARUH FASHION INVOLVEMENT DAN HEDONIC CONSUMPTION TENDENCY TERHADAP IMPULSE BUYING - Pangestu, I Kadek Bramantya Abdy; Santika, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
This study aims to determine the role of positive emotions mediating the influence of fashion involvement and hedonic consumption tendency on impulse buying. The sample measurements amounted to 105 respondents. Data collection is done by distributing questionnaires directly to customers of the Beachwalk Mall Bali fashion products. The analysis technique used is path analysis (path analysis) and sobel test. The test results show that there is a positive and significant influence between fashion involvement and hedonic consumption tendency towards positive emotions, a positive and significant influence between fashion involvement, hedonic consumption tendency and positive emotions on impulse buying. Positive emotions can act as a significant mediating variable between the influence of fashion involvement and hedonic consumption tendency towards impulse buying. These results mean that the higher fashion involvement and hedonic consumption tendency will be able to increase high positive emotions too, so that it can encourage impulse buying for customers of Beachwalk Mall Bali fashion products.